The Silk Road Growing Role of India - Mukesh Kumar Mishra (ZBW – Leibniz Information Centre for Economics, 2020)
The growing positive tendencies and various efforts towards revival of the Silk Route have been strongly supported by India. After initiating various efforts to revive ancient trade route. India is trying to follow the Silk Route as a metaphor of its economic and trade interests in Eurasia. South Asia can again be a hub of economic activities through improved connectivity, India must focus on improving connectivity along the ancient Silk Route in order to establish itself as a hub for Asia-Europe trade, "Reviving the Asian trade route would put South Asia at the centre of Europe and East Asia," India have to explore the full potential of the region. Now India's development experience and technologies can be valuable for other developing countries. These offices are striving to facilitate the sharing of experiences and knowledge between India and other developing countries in South Asia and beyond, which assists the group's member states in capacity building for transfer and development of technology. In the past two years, a new wind of regionalism has swept across Central Asia. This encouraging development follows years in which Central Asia, in part due to the paucity of regionalism among the region's states, was viewed mainly as an arena of competition among great powers. Too often, outsiders, including Westerners, have had a tendency to talk about Central Asia with others rather than to promote the agency of the region itself. That, however, is about to change. Central Asian leaders are coordinating policies more frequently with India, in more areas than ever, and are currently seeking ways to structure more developed forms of regional cooperation under the Indian actions and the nature and character of India's policy initiatives. The paper is organized as follows, briefly explores the Silk Roads and Indian bilateral relations with the Silk Route Countries since independence and discusses why India should consider actively participating in this zone as well as India's position on the matters.
Keywords: F; 330; The Silk Road; International Relations; International Economics; International Trade